PENILAIAN RISIKO PADA AKTIVITAS KEBERSIHAN DI LABORATORIUM FARMASETIKA JURUSAN FARMASI - FAIZAL RIZA SUHARTO (JURNAL INFO KESEHATAN, 2016)
It has been done a research with the title "assessment of the risk on the cleanliness activity in the laboratory pharmaceutical study program". Every activity has potential possibility happen a danger and impact of that event. In aspect K3, the factor of cleanliness is if not it managed correctly it can make an incident or hazard for the human, equipment, materials, and environment. This descriptive research, in general, has a purpose to know the risk of the cleanliness activities in a pharmaceutical laboratory. Population (object research) place: the laboratory pharmaceutical; subject: the person who has a responsibility in a laboratory, lecturer, laboratory assistant, and college student; activity: danger identification of activity cleanliness and interview. Sample (informant) is a college student who is involved in cleanliness activity. Technique sampling is a purposive namely who are involved in cleanliness activity in the laboratory. The researcher as an instrument adaptable with the informant and the cleanliness activity that is done by a college student. The technique of collecting data using checklist and interview with the informant to get the information of the finding of the checklist (a category not). Data analysis techniques are the from checklist then be made identification of dangerous activity and potential danger then calculated the value of risk and rank the risk. The result of the research shows that from the checklist (identification of hazards activity and potential hazards ) got value (Low < 3), include low risk it means that risk of cleanliness activity can be received and follow up by the monitoring from lecturer and the laboratory assistant to make sure that the control tool in the form of activity the form of making procedure or documentation system, administration, and the use of APD applied correctly.